Chief Nursing Officers: Their COVID-19 Experience. (14th May 2022) - Monroe, Martha; Davies, Claire C.; Beckman, Dee; Cantrell, Donita; Brockopp, Dorothy
Abstract : OBJECTIVE: The purpose of this study was to describe the experience of chief nursing officers (CNOs), including leadership strategies that they developed as they encountered the administrative challenges posed by COVID-19. BACKGROUND: The COVID-19 pandemic required CNOs to make difficult decisions and to support nursing staff as they cared for critically ill and dying patients, and therefore, they experienced intense stress during a pandemic of a highly infectious disease. Understanding the challenges that CNOs faced in this crisis will help hospitals and CNOs to better prepare for the future. METHODS: Using a descriptive qualitative approach, we conducted interviews with 9 CNOs from hospitals across the United States. The goal of the interviews was to develop an understanding of the difficulties that these CNOs encountered during the COVID-19 pandemic and their emotional response to the challenging situations. RESULTS: Themes of frustration, heartbreak, and feeling overwhelmed, exhausted, and helpless were revealed. In addition, pride in being a nurse was expressed. CONCLUSION: Themes revealed in this study suggested intentional leadership strategies that would be useful in future healthcare crises.